Maxim ojCooperation in Dialogue in a Japanese Novel Saga no Gabbai Bacchan (A Study of Novel Translation from Japanese to Bahasa Indonesia) Robihim - Robihim Robihim (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2016)
Generally novel tells us about the life that is around humans. In a novel, the author will always make every effort to direct the reader to the images of the reality of life through the stories contained in the novel, with a variety of unique and attractive packaging. In the novel Saga no Gabai Bacchan, communications are contains aspects of pragmatics, especially across languages and intercultural communication. The purpose of this study is to provide a thorough understanding of the maxims of cooperation with the principles of compliance and violations in the dialogue translation of the novel Saga no Gabai Bacchan. Due to this research, including the type of pragmatic research in translation, which reveal the pragmatic aspects of dialogue in the novel translation of Saga no Gabai Bacchan (SGB) from Japanese into Indonesian, this study used content analysis method (content analysis) with a pragmatic approach and translation. Content analysis method is used to reveal the pragmatic aspects of the dialogue translation of the novel SGB from Japanese into Indonesian who be related with maxims of cooperation, both of which meet the principles of cooperation and in violation of the principle of cooperation. So this research, including qualitative research with the analysis method as the container contents, we study the pragmatic aspects of the translation of the dialogue to understand the dialogue as a whole translation and translation analysis reveals speech translation, translation deviations and failures pragmaliguis in dialogue translation. The results were obtained descriptions of the data on the dialogue translation is identified based on the pragmatic aspects of the dialogue translation The pragmatic aspects include cooperation maxims which are divided into four categories, namely quantity maxim, maxim of quality, maxim implementation and maxim relevance. Each of these maxims emphasizing speakers within the limits of compliance and violation of the principles of communication in accordance with the situation and conditions speech act in the delivery of accurate information, clearly and information based on facts, not excessive, and not taxa/ambiguity. Novel umumnya menceritakan tentang kehidupan yang ada disekitar manusia. Dalam sebuah novel, pengarang akan selalu berusaha semaksimal mungkin untuk mengarahkan pembaca kepada gambaran-gambaran realita kehidupan melalui cerita yang terkandung dalam novel tersebut, dengan berbagai kemasan yang unik dan menarik. Dalam novel Saga no Gabai Bacchan, komunikasi yang disampaikan banyak mengandung aspek-aspek pragmatik. Hubungan antara pragmatik dapat dijelaskan melalui pemahaman bentuk tindak komunikasi, terutama komunikasi antarbahasa dan antarbudaya. Tujuan penelitian ini adalah memberikan pemahaman yang mendalam tentang maksim kerja sarna dengan prinsip pemenuhan dan pelanggaran dalam dialog pada novel Saga no Gabai Bacchan. Berhubung penelitian ini termasukjenis penelitian pragmatik, yaitu mengungkapkan aspek pragmatik dalam terjemahan dialog pada novel Saga no Gabai Bacchan (SGB) dari bahasa Jepang ke dalam bahasa Indonesia, maka penelitian ini menggunakan metode analisis isi (Content Analysis) dengan pendekatan pragmatik. Metode analisis isi digunakan untuk mengungkapkan aspek pragmatik dalam dialog pada novel Saga no Gabai Bacchan dari bahasa Jepang ke dalam bahasa Indonesia yang berkaiitan dengan maksim kerjasama. Jadi penelitian mengkaji aspek pragmatik pada dialog secara utuh, dan analisis mengungkapkan ujaran, penyimpangan dan kegagalan dalam dialog. Dari hasil penelitian diperoleh 4 katagori maksim, yaitu maksim kuantitas, maksim kualitas, maksim pelaksanaan dan maksim relevansi, masing-masing mengandung prinsip pemenuhan dan prinsip pelanggaran. Adapun tiap-tiap maksim ini menekankan penutur dalam batas-batas pemenuhan dan pelanggaran prinsip komunikasi sesuai dengan situasi utur dan kondisi tuturan dalam dalam penyampaian infonnasi yang akurat, jelas dan sesuai fakta, tidak berlebihan, berkaitan dan tidak taksa.